Genetic diversity of HPV-6 in concurrent multiple anogenital warts - Fujs Komloš, Kristina (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2013)
Introduction: Anogenital warts (AGW) are the most common benign tumors in the anogenital area. They are etiologically associated with alpha human papillomaviruses (HPV), in more than 90% of cases with HPV-6 and HPV-11. AGW frequently displays a multifocal and multicentric appearance. However, it is not clear whether the occurrence of multiple AGW in a particular patient is a consequence of infection with single or multiple HPV genomic variants of a given HPV genotype. Methods: Forty-five HPV-6 isolates from fresh-frozen AGW tissue specimens, obtained from 18 patients with concurrent multiple AGW, were included. The entire HPV-6 L1, E5a, E5b ORFs, and LCR genomic region was sequenced. Results: Fourteen different HPV-6 L1-LCR-E5a-E5b genomic variants were identified among 18 patients with concurrent multiple AGW. In 17 out of 18 patients, a single identical HPV-6 L1-E5a-E5b-LCR genomic variant was identified in all concurrent multiple AGW collected in an individual patient. Co-infection with two different HPV-6 genomic variants was identified in one patient. Discussion: The presence of an identical HPV genomic variant in all concurrently present multiple AGW within an individual patient supports the hypothesis that the occurrence of multiple concurrent AGW is a consequence of infection with a single HPV-6 genomic variant, rather than infection with multiple genomic variants of HPV-6.
Keywords: anogenitalne bradavice; genetics; genetika; HPV-6 virus